2017
DOI: 10.1016/j.jpeds.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease in Premature Infants 25-32 Weeks' Gestational Age

Abstract: Objective To determine the birth prevalence of congenital heart defects (CHDs) across the spectrum of common defects in very/extremely premature infants and to compare mortality rates between premature infants with and without CHDs. Study design The Kids' Inpatient Databases (2003-2012) were used to estimate the birth prevalence of CHDs (excluding patent ductus arteriosus) in very/extremely premature infants born between 25 and 32 weeks gestational age (GA). Birth prevalence was compared with term infants fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 24 publications
4
46
0
1
Order By: Relevance
“…Their results were consistent with a 2012 European study, which found that children with CHD (atrial septal defect and PDA) were twice as likely to be born prematurely (<37 weeks) or very/extremely prematurely (<32 weeks) than children without CHD . Additionally, Chu et al reported that the birth prevalence of severe defects was markedly higher for neonates born more prematurely: 8.8 at 35 to 36 weeks compared to 6.7 at 31 to 32 weeks per 1000 birth hospitalizations ( P = .05), and greater prematurity was also associated with higher mortality, with very/extremely premature neonates who had severe CHD at a 7.5‐fold increased adjusted odds ratio of death compared to those without CHD. Other unexpected findings identified in our study were 5 (3%) neonates with PH and 3 (2%) with pericardial effusions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Their results were consistent with a 2012 European study, which found that children with CHD (atrial septal defect and PDA) were twice as likely to be born prematurely (<37 weeks) or very/extremely prematurely (<32 weeks) than children without CHD . Additionally, Chu et al reported that the birth prevalence of severe defects was markedly higher for neonates born more prematurely: 8.8 at 35 to 36 weeks compared to 6.7 at 31 to 32 weeks per 1000 birth hospitalizations ( P = .05), and greater prematurity was also associated with higher mortality, with very/extremely premature neonates who had severe CHD at a 7.5‐fold increased adjusted odds ratio of death compared to those without CHD. Other unexpected findings identified in our study were 5 (3%) neonates with PH and 3 (2%) with pericardial effusions.…”
Section: Discussionsupporting
confidence: 80%
“…A recent study by Chu et al found that premature neonates had a significantly higher birth prevalence of severe CHD compared to term neonates (7.4 per 1000 very/premature births versus 1.5 per 1000 term births; P < 0.01). Their results were consistent with a 2012 European study, which found that children with CHD (atrial septal defect and PDA) were twice as likely to be born prematurely (<37 weeks) or very/extremely prematurely (<32 weeks) than children without CHD .…”
Section: Discussionmentioning
confidence: 94%
“…The in-hospital mortality of 25% and incidence of major neonatal morbidity (NEC, intraventricular haemorrhage (stage III or greater), periventricular leukomalacia, retinopathy of prematurity or bronchopulmonary dysplasia) of 44% in our study are similar to those previously reported 3 4. Given the retrospective nature and small population of our study, causation cannot be established.…”
supporting
confidence: 80%
“…The current study included a high proportion of infants (62%) diagnosed with ASDs, which are commonly diagnosed in premature infants (possibly because of the increased use of echocardiograms in this population), but are not typically associated with mortality at an early age. 22,26,27 In studies where the prevalence of ASD is lower, mortality at NICU discharge was 44%. 24 Similarly, when infants with isolated ASD diagnoses are excluded from the study, as was the case in a report from the Vermont Oxford Network, or Pediatrix Medical Group Data Warehouse, mortality was again higher at 44 and 55%, respectively.…”
Section: Discussionmentioning
confidence: 99%